Analysis of Broiler Chicken Business with Addition of Probiotics and Digestive Enzymes in Fermented Ration - Allaily Allaily; Andrie Wahyu Septian; Muhammad Daud (JURNAL ILMIAH PETERNAKAN TERPADU, 2022)
Broiler chicken business as a producer of animal protein sources in Indonesia is growing rapidly. Nevertheless, the high operating costs of broiler chickens, especially the cost of feed, are one of the factors that cause of breeder profits to be small. To produce high margins and reduce production costs, breeders need to look for feed materials that are cheap. The thing that can be done is to add feed additives in the form of probiotics and digestive enzymes in fermented rations. This study was conducted to review information about the addition of probiotics and digestive enzymes in rations in the maintenance of broiler chickens to the feasibility of broiler chicken maintenance efforts. The study used a Complete Randomized Design consisting of 5 treatments and 4 repeats, the study treatment were P0= without the addition of probiotics and digestive enzymes, P1 = 0.5% probiotics + 0% digestive enzymes, P2 = 0% probiotics + 0.5% digestive enzymes, P3 = 0.5% probiotics + 1% digestive enzymes, P4 = 1% probiotics + 0.5% digestive enzymes. Results from the study showed the addition of fermented rations without probiotics and 0.5% digestive enzymes (P2) is feasible and beneficial if run in the maintenance of broiler chickens. Rations with the addition of digestive enzymes by 0.5% are more beneficial than other rations treatments.